(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
In the early years of the Peoples Republic of China, Polish films were among the first foreign films to be introduced and dubbed for Chinese audiences. Between 1949 and 1966, a total of 35 Polish films were screened in China, encompassing a variety of genres such as newsreels, feature films, and documentaries, with both black-and-white and color productions. To a certain extent, Polish films helped Chinese audiences "construct an imagination of ’socialist countries’". This article focuses on Polish films introduced to China during this period, describing their historical context, selection criteria, promotional and screening strategies, and their impact on Chinese cinema and audiences. Through this exploration, the paper aims to outline the trajectory of Polish film screenings in China while offering insights into the characteristics and themes of imported films during the formative years of Chinese film dubbing.